Type of intraspecific and interspecific interaction among three heron species, while foraging around Pulau Dua Nature Reserve, Serang, Banten's province - DEWI ELFIDASARI (Biodiversitas Journal of Biological Diversity, 2007)
This research intends to know interaction type among three heron species while foraging around Pulau Dua Nature Reserve, SerangBanten's Province. Observational method that is utilized is direct observing up to 6 months, pictures taking supported watch utilizeHandycam by focal observation method, meanwhile data analyze was done by using scan sampling method. The researchâ€™s result points out that interaction during foraging for three species herons, namely Casmerodius albus, Egretta garzetta, and Bubulcus. Ibis, cover neutralism, competition and cooperation. C. albus showed cooperative's interaction as much as 66.67%. This interaction is happening between C. albus and Phalacrocorax sp. The competition and neutralism on C. albus each of them are 16.67%. E. garzetta showed neutralism as much as 50%, between E. garzetta and other waterbird which are Threskiornis melanocephalus and Plegadis falcinellus. Meanwhile, cooperative as high as 37.50% and competitions as high as 12.50%. B. ibis showed neutralism, as high as 44.44% between B. ibis and both Ardeola speciosa and P. falcinellus. Neutralism and competition interaction each of them are 33.33% and 22.22%.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: interaction, cooperation, neutralism, competition, heron.